A leitura crítica de notícias falsas na internet: uma proposta para os alunos finais do ensino fundamental - Michel Martins Lacerda Diogo (2019)
The paper investigates the contributions of a teaching project to the improvement of critical reading of fake news on the Internet among 9th grade students from the perspective of the researcher teacher. Digital Interaction and communication technologies have facilitated access to information, but require critical readers to avoid misinformation through phenomena such as fake news. This research is qualitative and considers concepts such as critical reading (BRAHIM, 2007, CASSANY & CASTELLÁ, 2010, SOUZA, 2011, MARINS-COSTA, 2016) and multi-literacy (ROJO, 2012). The analysis took place through the teaching project implemented in a public school in the city of Belo Horizonte. The actions were organized, firstly, by applying a questionnaire whose results made it possible to observe the students' profile in relation to Internet access habits, search for information and contact with fake news. Subsequently, the teaching project was applied through reading workshops with themes on Internet information, fake news characteristics, elements of journalism and, soon after, the differences between fake news and reliable journalism. The last stage consisted of the production of texts for social networks in order to alert the school community about the importance of critical reading of news on the Internet. The project provided students with improved reading skills through activities such as the recognition of details that highlight fake texts on the Internet, the importance of fact checking, and the distinction between reliable fake news journalism. Thus, it was possible to develop criticality in relation to news circulating on the network, as well as on ethics and responsibility interactions on the Internet.